The Estimation of Vibrational Energy of Two Coupled (Welded) Plates Using Statistical Energy Analysis - Mohammed, Adnan D.; Ibraham, Hawraa S. (Al-Khwarizmi Engineering Journal, 2011)
This paper deals with a method called Statistical Energy Analysis that can be applied to the mechanical and acoustical systems like buildings, bridges and aircrafts …etc. S.E.A as a tool can be applied to the resonant systems in the circumstances of high frequency or/and complex structure». The parameters of S.E.A such as coupling loss factor, internal loss factor, modal density and input power are clarified in this work ; coupled plate sub-systems and explanations are presented for these parameters. The developed system is assumed to be resonant, conservative, linear and there is an equipartition of energy between all the resonant modes within a given frequency band in a given sub-system. The aim of this work is to find the energy stored in the sub-systems for two coupled (welded) plates in rectangular angle systems and study the effect of changing sub-systems dimensions, the results shows that as surface area of directly driven plates A1 increases energy level of plate 1 increases while a reduction in the energy level of indirectly driven plate (plate 2) is noticed. This is because of the strength of coupling decreases towards the weak coupling condition and this leads to a reduction in the power transferred from plate 1 to plate 2 and consequently a lower energy level for plate 2. In addition the effect of changing the internal loss factor for a range of (0.00001-0.1) causes a reduction of the values of energy level in these sub-systems. because the increasing of internal loss factor values led to the increasing of the material resistance and that will dissipate the energy flow across those sub-systems. A comparison is made between S.E.A models built by FORTRAN program and Finite Element model solved by ANSYS package.